Respuesta :
Answer:x to the power of 2 plus 2x=-6
Step-by-step explanation:
Answer:
[tex]\sf x = -1 + \sqrt{5}\:i,\: -1 - \sqrt{5}\:i[/tex]
Explanation:
[tex]\sf \rightarrow x^2 + 2x +6 = 0[/tex]
[tex]\sf use\:quadratic\:formula: x = \dfrac{ -b \pm \sqrt{b^2 - 4ac}}{2a} \quad when \: \: ax^2 + bx + c = 0[/tex]
comparing identify:
- a = 1, b = 2, c = 6
Substitute inside the formula:
[tex]\rightarrow \sf x = \dfrac{ -2 \pm \sqrt{2^2 - 4(1)(6)}}{2(1)}[/tex]
evaluate:
[tex]\rightarrow \sf x = \dfrac{ -2 \pm \sqrt{4 - 24}}{2}[/tex]
[tex]\rightarrow \sf x = \dfrac{ -2 \pm \sqrt{- 20}}{2}[/tex]
[tex]\rightarrow \sf x = \dfrac{ -2 \pm 2\sqrt{5}\:i}{2}[/tex]
[tex]\rightarrow \sf x =-1 \pm \sqrt{5}\:i[/tex]
[tex]\rightarrow \sf x = -1 + \sqrt{5}\:i,\: -1 - \sqrt{5}\:i[/tex]